(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Low back Myofascial pain syndrome is a disorder triggering pain at myofascial trigger points and appears to be the most frequent source of pain in clinical practice. Active release technique and myofascial release both help in improving low back myofascial pain. Purpose: This study aimed to compare the effect of active release against trigger point release technique in low back myofascial pain syndrome. Methods: Forty-five male and female participants with low back myofascial pain syndrome participated in the current study had been divided into three groups randomly. Group A obtained active release technique for myofascial trigger points of Iliocostalis Lambourum and Gluteus Medius muscle, and traditional physiotherapy. Group B obtained myofascial release for trigger point of Iliocostalis and Gletus Medius, and traditional physiotherapy. Group C (control group) obtained traditional physiotherapy only in the form of stretching and strengthening exercises. The treatment was conducted two sessions per week for one month. The Wagner FPX25 digital Algometer was utilized to evaluate pain pressure threshold and Ronald Morris disability Questionnaire to measure function disability of back. It is a self-reported questionnaire. Results: no substantial difference has been detected among groups pre-treatment (p > 0.05). Comparison among groups, post treatment, showed a substantial improvement in the PPT of trigger point of Iliocostalis and Gluteus Medius muscle and a significant decrease of Ronald Morris disability Questionnaire score in group A as compared to that of group B (p > 0.01) and group C (p > 0.01). Conclusion: The active release technique improves tolerance of trigger points of Iliocostalis and Gluteus Medius more than myofascial release and improves back function more than myofascial release in low back myofascial pain syndrome.